(3GdJhTjM GdePgH aj JUMjM GdegPHs - (3TgGH GdOjf CHi GdYHGS CMeO Hf dDdD GdTgjQ HGHf GdfbjH GdeUQj GdTGaYjs; (3GdajQhRGHGOj GdTjQGRj , CHh ESMb EHQGgje Hf Ydj GdTjQGRj, CHh GSMGb , LeGd GdOjf,J (B476 (3g` s
(3ChdgG (B:s
(3CeG HYO abO SCdfi HYV CUMGHi Cf CVY JUMjMkG Ydi GdegPH ai Gdabg ddTjN CHj GSMb GdTQGRi s
(3BNQgG (B:s
(3hcPdc Mce GdChSW hGdCUZQ Je GdcJGH HMeO Gddg JYdi s
(3GdegPH ai GdaQhY ddTjQGRi GfXQ cTa GdXfhf L(B2 (3U` (B1912s
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdTGaYjs